Analysis of Open-Source CASE Tools for Supporting Software Modeling Process with UML - Freire, Emmanuel Sávio Silva; Oliveira, Gabriel Cavalcante; Gomes, Maria Eurizene de Sousa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Good modeling practices or guidelines guide the construction of UML diagrams allowing higher quality software. When these guidelines are mapping in a CASE tool, they can support the creation of models following the UML syntax. Thus, this article aimed to verify the guidelines addressed by the open-source CASE tools that allow the creation of the five most used UML diagrams by software engineers. Therefore, thirteen tools were analyzed: ArgoUML, StarUML, UMLet, DiaUML, BOUML, Violet, UML Designer, Modelio, NClass, Plantuml, Umbrello, Open ModelSphere, and Papyrus. As results, it was found that StarUML and UML Designer attended the highest number of good practices. Although all diagrams were considered by these tools, Use Case and Sequence UML diagrams were the ones that had the most good practices numbers attended.